An improved method for determining the position of overlying separated strata in mining. (January 2018) - He, Jiang-Hui; Li, Wen-ping; Liu, Yu; Yang, Zhi; Liu, Shi-Liang; Li, Luan-Fei
Abstract: Water bursts and flooding from overlying separated strata are new types of roof water hazards in coal mining in China. Over the past decade, there have been several major outbursts of water from overlaying separated strata. Accurate determination of the location of separated strata is a prerequisite for preventing and controlling such outbursts. The traditional method of determining the location of separated strata is based on the composite-beam principle, but it still has theoretical defects. To address the shortcomings of this method, we propose an improved method for determining the location of the separated layers, namely, the stepwise comparison combination method (SCCM). SCCM can be used to determine the location of separated strata by comparing the curvature between adjacent rock layers at the same level and dividing the composite beam accurately at each level. The improved method not only considers the interaction of all strata and the influence of any rock stratum on the overall deformation of overlying strata, but also considers local interactions between adjacent strata. By stepwise comparison and combination, the actual combined status of the overlying section can be determined, and the calculated position of separated strata is more accurate. The traditional method and the improved method were used to calculate and determine the location of separated strata in a real mining example. Field explorations confirmed that the results from the improved method described in this paper were more accurate. Highlights: Shortcomings of the traditional method of determining the separated strata were analyzed. An improved method of determining the location of the separated strata is proposed. By stepwise comparison and combination, the actual combined state of the rock strata can be demonstrated. Distribution characteristics of separated strata in overlying strata are obtained.